Analysis of some problems in test on discrete mathematics - Krylovas, Aleksandras; Subač, Olga (Lietuvos matematikos rinkinys, 2023)
In this article some problems in test on discrete mathematics are analyzed. Using statistics of students results we present several problems that presence in test could be more or less advisable.
Keywords: statistic education research; student achievement; mathematics teaching